Anatomical insights into the adaptability and invasiveness of Humulus scandens in Romanian flora - Mioara DUMITRAŞCU; Alina G. CÎŞLARIU; Daniela C. MIHAI; Anca SÂRBU (Notulae Scientia Biologicae, 2024)
The negative impact of invasive alien species on biodiversity, agriculture, ecosystem services, and human well-being is a significant concern for scientists. Despite extensive research in the past decade to understand their effects on native communities and ecosystems, predicting and managing future invasions remains challenging. Humulus scandens, a species native to Asia, was introduced to Europe in 1880 for ornamental purposes. This vigorous climbing vine thrives in wetlands, riparian habitats (especially river and stream sides), and ruderal habitats (roadsides, wastelands, abandoned, and disturbed areas). Our research aimed to investigate the vegetative body structure of H. scandens to understand its high resilience in Romanian habitats. The structural characterization of the vegetative organs involved detailed microscopic examination of the coloured cross-sections. The results revealed a well-developed secondary structure of the root and stem, granting robustness and resistance to the plant, favouring it in competition with other species for environmental resources.